Characteristics Associated With Treatment Failure 1 Year After Midurethral Sling in Women With Mixed Urinary Incontinence. Issue 2 (August 2021) - Sung, Vivian W.; Richter, Holly E.; Moalli, Pamela; Weidner, Alison C.; Nguyen, John N.; Smith, Ariana L.; Dunivan, Gena; Ridgeway, Beri; Borello-France, Diane; Newman, Diane K.; Mazloomdoost, Donna; Carper, Benjamin; et al.
Abstract : OBJECTIVE: To evaluate characteristics associated with treatment failure 1 year after midurethral sling in women with mixed urinary incontinence. METHODS: Four-hundred three women who participated in a randomized trial that compared midurethral sling and behavioral and pelvic floor muscle therapy (combined group) compared with midurethral sling alone for mixed incontinence with 1-year follow-up data were eligible for this planned secondary analysis. Overall treatment failure was defined as meeting criteria for subjective or objective failure or both. Subjective failure was defined as not meeting the minimal clinical important difference for improvement on the UDI (Urogenital Distress Inventory) total score (26.1 points). Objective failure was defined as not achieving 70% improvement on mean incontinence episodes of any type per day or having undergone any additional treatment for persistent urinary symptoms at 12 months postoperative. Logistic regression models for treatment failure were constructed. Independent variables included site and treatment group, and clinical and demographic variables based on bivariate comparisons ( P <.2). Treatment group interaction effects were evaluated. RESULTS: One hundred twelve of 379 (29.6%) women had overall treatment failure, with 56 of 379 (14.7%) undergoing additional treatment but only two needing intervention for stress incontinence. Previous overactive bladder (OAB) medication (unadjusted odds ratio [OR] 2.19, adjusted odds ratio [aOR] 1.96, 95% CI 1.17–3.31); detrusor overactivity on cystometrogram (OR 2.25, aOR 2.82, 95% CI 1.60–4.97); and higher volume at first urge (OR 1.03, aOR 1.04, 95% CI 1.01–1.07) were associated with overall failure. Worse UDI-urgency scores were associated with failure, with an added interaction effect in the midurethral sling–alone group. CONCLUSIONS: Certain clinical and urodynamic variables are associated with treatment failure after midurethral sling in women with mixed urinary incontinence. Women with more severe urgency symptoms at baseline may benefit from perioperative behavioral and pelvic floor muscle therapy combined with midurethral sling. Overall, the need for additional urinary treatment was low and primarily for OAB. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT01959347. Abstract : Prior overactive bladder medication use, detrusor overactivity, and urgency scores were associated with persistent urinary symptoms after midurethral sling in women with mixed urinary incontinence.